2022
DOI: 10.3390/cancers14205158
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Therapy after Progression on Immune Checkpoint Inhibitors in MSI Metastatic Gastrointestinal Cancer Patients: A Multicenter Retrospective Cohort Study

Abstract: Background: In microsatellite instability (MSI)/mismatch repair-deficient (dMMR) gastrointestinal cancers, the optimum therapy after the progression of immune checkpoint inhibitors (ICIs) is yet unknown. Here, we compared the efficacy of programmed death 1 (PD1)/programmed death ligand-1 (PD-L1) inhibitors plus other therapy and chemotherapy with or without targeted therapy in MSI/dMMR gastrointestinal cancer patients after progression on anti-PD1/PD-L1 monotherapy. Methods: We retrospectively recruited MSI/dM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The second strategy involves use of ICI in combination with other therapies, such as targeted therapy and chemotherapy or dual immunotherapy. A retrospective study showed that combining ICI with other treatments (e.g., anti-angiogenesis therapy in 15 patients and chemotherapy in 9 patients) resulted in better clinical outcomes compared to chemotherapy with or without targeted therapy for patients with MSI-H GI cancer who had progressed on ICIs 20 . Prospective studies have shown limited clinical benefit when combining anti-PD-L1 with TGF-β bifunctional fusion protein inhibitor (0% ORR) and anti-TIM3 (4.5% ORR) in patients with ICI-resistant MSI-H CRC 21 , 22 .…”
Section: Icis For Dmmr/msi-h Mcrcmentioning
confidence: 99%
“…The second strategy involves use of ICI in combination with other therapies, such as targeted therapy and chemotherapy or dual immunotherapy. A retrospective study showed that combining ICI with other treatments (e.g., anti-angiogenesis therapy in 15 patients and chemotherapy in 9 patients) resulted in better clinical outcomes compared to chemotherapy with or without targeted therapy for patients with MSI-H GI cancer who had progressed on ICIs 20 . Prospective studies have shown limited clinical benefit when combining anti-PD-L1 with TGF-β bifunctional fusion protein inhibitor (0% ORR) and anti-TIM3 (4.5% ORR) in patients with ICI-resistant MSI-H CRC 21 , 22 .…”
Section: Icis For Dmmr/msi-h Mcrcmentioning
confidence: 99%
“… 10 It was reported in a retrospective study that patients with MSI/dMMR gastrointestinal cancer who had progressed on PD-1/PD-L1 inhibitors could still benefit from anti–PD-1/PD-L1 plus chemotherapy. 11 Recently, the combination strategy of anti–PD-1/PD-L1 and chemotherapy has been proven to be more effective than chemotherapy and as the standard of care in many cancers, including lung cancer, GC, and esophagus cancer. 12 - 15 Notably, in non–small-cell lung cancer (NSCLC), the PFS and OS curves of anti–PD-1/PD-L1 versus chemotherapy were always crossed in prior studies.…”
Section: Introductionmentioning
confidence: 99%